Different histories, similar opinions? Perspectives of presidents of public and private universities on Argentina’s higher education system - Arias, María Fernanda (Education Policy Analysis Archives, 2010)
This article analyzes the opinions about the system of higher education in Argentina of presidents of private and public universities. The sample consisted of sixteen in-depth interviews with presidents of public and private universities. In the 1990s Argentina, similarly to other Latin American and European countries, initiated profound reforms of its university system The analysis of the interviews shows, that although Argentina's higher education system was traditionally organized around the ethos of public universities and only recently a new but increasingly influential private sector was developed, the opinions of the presidents of both types of universities is rather similar.. We concluded that the type of governance, public or private, is not the most influential dynamic in the opinions of the presidents of these universities, but the particular history and institutional traditions are better explanatory variables.